The internationalization of European sports teams and the issue of national citizenship : can sports transcend political borders? - Alberts, Heike C. (E. Mellen Press, 2011)
The migration of professional soccer players to European countries is not a new phenomenon, but the volume and composition of these flows have changed substantially since the 1990s, when a court ruling established that restrictions on players from other European Union countries violate European Union law. This court ruling not only dramatically changed the national composition of Western European soccer teams, but also of volleyball and handball teams. using geographic techniques, this book investigates current migration patterns of professional players to Western European soccer, volleyball a.